Description and anatomical evaluation of lesions of mandibular osteomyelitis in alpacas (Vicugna pacos) - Pezo C., Danilo (2017)
The anatomopathological lesions of clinical cases of osteomyelitis in 21 adult alpacas, six tuis and three baby alpacas were described through clinical and pathological evaluation, determining the number, degree, and progression of the lesions. Alterations of the molar part, edentulous space, and incisive part of the buccal and lingual sides of the left and right mandibular body were observed. In all cases, the lesions appeared in the mandible, mostly on the left side. Osteomyelitis was predominantly severe in the youngest alpacas, where hyperostosis, rarefaction, necrosis, involvement, and sequestration develops in less time than in adults and tuis. Mild lesions were thickened in the left mandible, while moderate and severe lesions were multifocal on both sides, with ulcerations and fistulas directly related to the progression of lesions.